Touching Books, Touching Art: Tactile Dimensions of Sacred Books in the Medieval West. Issue 1 (3rd July 2017) - Ganz, David
Abstract : This essay deals with the role of book decoration in a tactile approach to sacred texts in the Western Middle Ages. For a long time, books and artworks have been discussed as visual objects. Taking into account their intrinsic haptic qualities opens new ways to understand the contribution of the arts to the use of sacred texts in medieval Christianity.